2004
DOI: 10.1097/01.coc.0000128722.41587.19
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin, Cisplatin, and Raltitrexed in Patients With Advanced Gastric and Hepatobiliary Carcinoma

Abstract: The combination of epirubicin, cisplatin, and protracted venous-infusion 5-fluorouracil is the standard treatment of advanced gastric carcinoma in many European countries, and it is also an active regimen in hepatobiliary tumors. Raltitrexed is a specific inhibitor of thymidylate synthase with clinical activity in gastrointestinal malignancies. The aim of the study was to evaluate the clinical activity and toxicity of the combination of epirubicin, cisplatin, and raltitrexed in patients with advanced gastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Occasional studies have included raltitrexed, a chemotherapeutic drug with a long half-life, in the treatment combination used for intravenous chemotherapy of gastric cancer [ 17 , 18 ]. In those cases, the intravenous dosing regimens range from 1 mg/m 2 to 3 mg/ml 2 and were well tolerated, although one study suggested that there was no substantial antitumor activity using raltitrexed for gastric cancer intravenously [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Occasional studies have included raltitrexed, a chemotherapeutic drug with a long half-life, in the treatment combination used for intravenous chemotherapy of gastric cancer [ 17 , 18 ]. In those cases, the intravenous dosing regimens range from 1 mg/m 2 to 3 mg/ml 2 and were well tolerated, although one study suggested that there was no substantial antitumor activity using raltitrexed for gastric cancer intravenously [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For cancer patients with f luoropyrimidine-induced cardiotoxicity or a history of cardiac disease, raltitrexed may be a suitable alternative to 5-FU (18). In addition to patients with colorectal cancer, certain patients with advanced gastric cancer have benefited from treatment with raltitrexed and have demonstrated good tolerance to raltitrexed with low cardiac toxicity (21,22). However, the anticancer effect of raltitrexed for advanced gastric cancer remains unknown with regard to the pro-apoptotic mechanisms.…”
mentioning
confidence: 99%
“…The results have been summarized in Table 2. There were two phase I studies (14,15) and four phase II studies (16)(17)(18)(19), although two contain patients in the second-line of treatment. The phase I studies combined raltitrexed, at 3 mg/m 2 every three weeks, with an anthracycline; one study also included cisplatin (14).…”
Section: Discussionmentioning
confidence: 99%